The fabulous Dorseys - Green, Alfred E., 1889-1960; Dorsey, Jimmy, 1904-1957; Dorsey, Tommy, 1905-1956; Blair, Janet; Embassy Productions; Charles R. Rogers Productions; Cinetel Films ([Los Angeles, CA] : Embassy Productions, Inc., 1947)
Music and movie fans alike cheered this Hollywood adaptation of the real-life tale of brothers Tommy and Jimmy Dorsey, and its top-drawer musical numbers. Starring as themselves with actors filling out the remaining roles, these two icons of Big Band, Jazz, and Swing recount the rise and fall of their careers, and the long-running feud that threatened to keep them from ever performing together again.
Released thru United Artists.
Tommy Dorsey, Jimmy Dorsey, Janet Blair, Paul Whiteman, William Lundigan.
Director of photography, James Van Trees; editor, George M. Arthur; music, Louis Forbes, Leo Shuken.
In English or Spanish; with optional Spanish subtitles.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed August 7, 2015)
Keywords: Dorsey, Tommy, -- 1905-1956 -- Drama; Dorsey, Jimmy, -- 1904-1957 -- Drama; Musicians -- Drama; Biographical films; Feature films; Musical films; Internet videos; Streaming video